Orthopaedic manifestations of pseudoachondroplasia. (August 2019) - Weiner, D. S.; Guirguis, J.; Makowski, M.; Testa, S.; Shauver, L.; Morgan, D.
Abstract: Purpose: In 1959, Maroteaux and Lamy initially designated pseudoachondroplasia as a distinct dysplasia different from achondroplasia the most common form of skeletal dysplasia. Pseudoachondroplasia is caused by a mutation in the collagen oligomeric matrix protein gene (COMP) gene on chromosome 19p13.1-p12 encoding the COMP. The COMP gene mutations result in rendering the articular and growth plate cartilages incapable of withstanding routine biomechanical loads with resultant deformity of the joints. The purpose of the study was to characterize the typical orthopaedic findings in pseudoachondroplasia. Methods: The charts and radiographs of 141 patients with pseudoachondroplasia were analyzed. This cohort, to our knowledge, represents the largest group of patients describing the typical orthopaedic manifestations of pseudoachondroplasia. Results: Patients with pseudoachondroplasia have normal craniofacial appearance with normal intelligence. Short stature is not present at birth and generally appears by two to four years of age. The condition is a form of spondyloepiphyseal dysplasia and the long bones are characterized by dysplastic changes in the epiphysis, metaphysis and vertebral bodies. Radiographically the long bones have altered the appearance and structure of the epiphyses with small irregularly formed or fragmented epiphyses or flattening. The metaphyseal regions of the long bones show flaring, widening or 'trumpeting'. The cervical (89%) and thoracic and lumbar vertebrae show either platyspondyly, ovoid, 'cod-fish' deformity or anterior 'beaking'. Kyphosis (28%), scoliosis (58%) and lumbar lordosis (100%) are commonly seen. The femoral head and acetabulum are severely dysplastic (100%). The knees show either genu valgum (22%), genu varum (56%) or 'windswept' deformity (22%). Conclusion: Most commonly these distortions of the appendicular and the axial skeleton lead to premature arthritis particularly of the hips and often the knees not uncommonly in the 20- to 30-year-old age group. Level of Evidence: III